Students’ e-learning acceptance: Empirical evidence from higher learning institutions - Imran Mehboob Shaikh; Geoffrey Harvey Tanakinjal; Hanudin Amin; Kamaruzaman Noordin; Junaid Shaikh (Emerald Publishing Limited, 2024)
Purpose The purpose of this paper is to investigate the factors that influence business students’ adoption of e-learning systems by merging innovation diffusion theory (IDT) and the teaching for professional competence model (TPCM). Design/methodology/approach Snowball sampling was used to conduct the survey. In addition, 217 responses were obtained from students at private educational institutions. Similarly, literature on the determinants of e-learning adoption, TPCM, and IDT were reviewed to contribute to the factors that are instrumental in determining e-learning systems adoption. Findings The findings of the study show that e-learning systems adoption is influenced by factors such as online collaborative learning (OCL) and technology self-efficacy. Above all, the OCL variable was found to be influential in determining students’ adoption of e-learning systems platforms. On the contrary, perceived attributes such as perceived compatibility and perceived relative advantage were found not to be significant determinants of e-learning systems adoption. Research limitations/implications This study contributed not only to the theoretical extensions but also to practical implications, which would benefit the policymakers of higher education providers in terms of e-learning system adoption in the country. Originality/value IDT and TPCM models are evaluated alongside additional variables, namely, OCL and technology self-efficacy. As a result, this paper will serve as a useful reference guide for academicians, higher education administrators, and future researchers.